Pembelajaran Kimia Topik Asam Karboksilat dan Ester Terintegrasi Pembelajaran Sosial Emosional pada Murid Kelas XII MIPA SMA Negeri 1 Bone Tahun Pelajaran 2022/2023 - Ningsi, Surya (Chemistry Education Review (CER), 2023)
Every teacher certainly wants to see students more focused and enthusiastic in learning. As a teacher, of course you feel restless and anxious to see students who are less focused and tend to get bored when studying. Thus, teachers always strive to create fun and meaningful learning to motivate students to learn. One of the efforts made to increase student learning motivation is through social emotional learning. Social Emotional Learning (PSE) is learning in understanding, experiencing, managing emotions and achieving positive goals as well as learning that teaches how to feel and show empathy for others as well as build and maintain positive relationships or be skilled in making responsible decisions. PSE is very important for everyone to learn and understand. For teachers, integrating social-emotional learning in learning chemistry on the topic Carboxylic acids and esters is very helpful for students in learning chemistry. This learning was carried out for class XII MIPA students in Even Semester for the 2022/2023 Academic Year at SMA Negeri 1 Bone. Includes learning with the STOP Technique (breathing with full awareness) at the beginning of learning. Furthermore, Finger Painting Techniques are the core learning activities and end with Active Communication Role Play activities by sharing experiences and Reflections. By integrating PSE both at the beginning of learning, the core and the end of learning can have a positive impact on encouraging students to learn to be more enthusiastic, happy, confident and focused on learning and improving student relationship skills.